Analysis of Infusion and Ethanol Extract of Tamarindus indica L, Scurrula Sp, Mimosa pudica D of Fresh and Dry as Amylase Enzyme Inhibitor - Devi. Sy, Silvera; Nst, Musyirna Rahmah; Jannah, Ninuk Rodhiatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
α-amilase is one of digestive enzyme that hydrolize starch to maltose by α-glukosidase and degradation to form a glucose and continue with blood adsorption through villi of small intestine. Consomption of acarbose drug is one of ways for diabetic treatment to inhibit the activity of α-amilase. Tamarind leaves (Tamarindus indica L) herbal benalu api (Scurrula Sp) and herbal putri malu (Mimosa pudica D) regularly used as medical plant with activity of antidiabetic medicine. The aims of this studies was to analyze the potency of three medical plant with form of infusa and ethanol extract from fresh or dried plant to inhibit activity of α-amilase and akarbose used as positive control. Inhibition potency of sample against activity of α-amilase were determine base on maltose produced by of starch hydrolysis α-amilase to reduction dinitrosalicylic acid become 3-amino-5-nitrosalicylic acid and the absorbance were measured with spektrofotometer at 530 nm. Resulted of percentage inhibition against activity of α-amilase were herbal infusa from dried benalu api 85.58 ± 2,93%, infusa of fresh putri malu 87.40 ± 1,81%, and the dried 98,85 ± 0,66%. These results did not significancy different with inhibition of akarbose 93.89 + 0,02%. Infusa herbal of dried benalu api, fresh and dried putri malu were potential cover for acarbose to used as alternative medicine.